PERANCANGAN SETTING PANGGUNG MUSIK â€œEMPTY SPACES: TRIBUTE TO LINKIN PARKâ€ - Al Anshari, Umair; Tornado, Anggiat; Sriwardani, Nani (ATRAT: Jurnal Seni Rupa, 2017)
Most stages of Linkin Park single concerts were designed with dystopian themes that showed dark space and gloomy atmosphere. Yet, a music performance entitled â€œEmpty Spaces: Tribute to Linking Parkâ€was intended to develop and create a different concept of music stage design though it still used dystopian theme. Dystopia is taken from a science fiction work by Thomas Moore. This stage design was aimed to find out how much did the stage setting give added value and selling point to the music performed. This music performance is an appreciation and a tribute to Linkin Park for their 15-year career in music. Besides, it was held to entertain Linkin Park fans or are better known as Linkin Park underground, especially in Bandung.Keywords: Stage Design, Empty Spaces, Dystopia________________________________________________________________Banyak setting panggung dari konser tunggal Linkin Park mengangkat tema dystopia dengan bentuk ruang yang gelap dan suasana yang suram. Namun pertunjukan musik berjudul â€œEmpty Spaces: Tribute to Linkin Parkâ€ bertujuan untuk mengembangkan serta menciptakan konsep desain panggung musik yang berbeda walaupun masih satu tema dystopia. Dystopia diambil dari buku Scient Fiction karya Thomas Moore. Perancangan ini mencoba melihat seberapa besar daya nilai tambah dan nilai jual setting panggung terhadap musik yang ditampilkan. Tujuan dari pertunjukan musik ini ialah bentuk penghargaan serta persembahan terhadap grup musik Linkin Park atas eksistensinya di dunia musik Internasional selama 15 tahun lebih. Terlebih lagi untuk memberikan hiburan kepada pencinta Linkin Park atau biasa disebut Linkin Park Underground, khususnya di kota Bandung.Kata Kunci: Perancangan Panggung, Ruang Kosong, Distopia